Three risks for the German residential property market - Michael Voigtländer (Institut der deutschen Wirtschaft (IW), 2017)
With prices surging in major cities since 2010, the debate about a potential speculative bubble in the German housing market has been gaining momentum. Overall, however, the German housing market is sound. Neither an excess of construction, nor an excess of mortgage lending have been observed, and thus the risk of a sudden burst in housing prices seems low. In the major cities in particular, there is a discrepancy between supply and demand. Combined with low mortgage rates, strong price increases are plausible. Nevertheless, this study also points to risks in the market. Specifically, investors should take into account the 3 following risks: 1. In rural regions, there is an excess of supply of single-family homes. Since demographic forecasts for the larger part of these regions are dismal, a price correction seems more likely. 2. In some big cities, completions in micro apartments have been enormously high. Moreover, most new micro apartments are let at high rental rates, overburdening most students who are meant to be the typical users. As the population aged between 18 and 25 is set to shrink over the coming years, there are grounds for a market correction, 3. Multipliers indicate optimistic expectations with regards to future rent increases, specifically in Hamburg and Munich. Although rental increases can be justified by a growing population, there is a risk of a tightening in rental regulation, preventing investors from putting rental increases in practice. The German housing market appeared to be a haven for investors in recent years. The combination of high demand (migration), a robust economy and ultra-low mortgage rates offered the chance for high capital growth. Fortunately, the German market is less prone to overheating than other markets, but risks are emerging nonetheless. However, since demand continues to outpace supply in various sub-segments of the housing market, investment opportunities are still present.
Keywords: D53; R21; R31; 330